PANoptosis in neurological disorders: mechanisms, implications, and therapeutic potential - Li, Jingyi; Qu, Yi (Frontiers in Immunology, 2025)
PANoptosis is a unique form of programmed cell death (PCD) that has the combined main features of pyroptosis, apoptosis, and necroptosis, but cannot be fully explained by any single pathway alone. Among all the influencing factors in PANoptosis, the activation and assembly of PANoptosomes are the most critical. To date, four distinct PANoptosomes have been identified: Z-DNA-binding protein 1 (ZBP1), absent in melanoma 2 (AIM2), receptor-interacting protein kinase 1 (RIPK1), and nucleotide-binding leucine-rich repeat-containing receptor 12 (NLRP12) PANoptosomes. Currently, PANoptosis is a promising target for central nervous system (CNS) disorders treatment. Understanding its mechanisms will facilitate its therapeutic application. This review introduces the concept of PANoptosis, its detection methods, the molecular composition and regulation of PANoptosomes, and the role of ninjurin 1 (NINJ1), a new “executor” in PANoptosis. In addition, recent therapeutic advances targeting PANoptosis in CNS diseases were also discussed. Future research on inhibiting PANoptosis, the dynamic regulatory relationships among three death pathways, and the interactions with NINJ1 will offer new clinical insights.